2021
DOI: 10.1002/jper.20-0591
|View full text |Cite
|
Sign up to set email alerts
|

Individual predisposition and the intricate interplay between systemic biomarkers and periodontal risk in a general population

Abstract: Background Increasing age is associated with systemic diseases as well as with periodontal diseases. We wondered whether a biological age score constructed exclusively from systemic biomarkers would reflect periodontal risk factors at baseline and tooth loss as well as periodontal outcome during 10 years follow‐up. Methods From the Study of Health in Pomerania (SHIP) 2256 participants (1072 male, 1184 female) were studied for the relationship of the systemic biomarkers glycated hemoglobin (HbA1c), low density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Chou et al., reported results in Taiwanese adult population, treated for periodontitis, with a slight but significant risk association between treated severe periodontitis and MACEs in patients older than 60 years and not in patients younger than this age, 38 these authors, however, they included two events, malignant dysrhythmia and thrombolysis, which we did not include in our study. Other studies have recently described that the heterogeneity often found in the periodontitis and systemic diseases association might be explained by a combination of genetic, environmental and behavioral factors that constitute a biological age, that may be different to the most used chronological one in each patient 39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chou et al., reported results in Taiwanese adult population, treated for periodontitis, with a slight but significant risk association between treated severe periodontitis and MACEs in patients older than 60 years and not in patients younger than this age, 38 these authors, however, they included two events, malignant dysrhythmia and thrombolysis, which we did not include in our study. Other studies have recently described that the heterogeneity often found in the periodontitis and systemic diseases association might be explained by a combination of genetic, environmental and behavioral factors that constitute a biological age, that may be different to the most used chronological one in each patient 39 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have recently described that the heterogeneity often found in the periodontitis and systemic diseases association might be explained by a combination of genetic, environmental and behavioral factors that constitute a biological age, that may be different to the most used chronological one in each patient. 39 The relationship of patients with a single pathology (periodontitis or ED) and the occurrence of serious cardiovascular events and/or MACEs have been recently studied. A prospective 3-year study performed on German population did not find any statistical significance when analyzing the occurrence of a composite endpoint of several CVD similar to MACEs in patients with periodontitis, although patients with severe periodontitis achieved this combined CVD endpoint more often (HR = 1.05) and other periodontal parameters where statistically significant such as BoP and missing teeth.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the use of parameters that are phenotypic signs of periodontitis (clinical attachment loss; CAL), the same authors elaborated a subsequent model that accounted for systemic variables (Meisel et al 2021). A composite age predictor based on low-density lipoprotein cholesterol, fibrinogen, glycated hemoglobin, blood pressure, waist circumference, and white cells count was able to predict the risk for periodontitis in the same population.…”
Section: Periodontitis and Accelerated Aging: Clinical And Epidemiological Evidencementioning
confidence: 99%